2022
DOI: 10.1021/acs.analchem.1c05272
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Dual-Collision Energy Scanning Mass Spectrometry Approach: Discovery of Novel Microbial Bile-Acid Conjugates

Abstract: Bile acids (BAs) are a type of gut microbiota–host cometabolites with abundant structural diversity, and they play critical roles in maintaining host–microbiota homeostasis. In this study, we developed a new N-(4-aminomethylphenyl) pyridinium (AMPP) derivatization-assisted alternating dual-collision energy scanning mass spectrometry (AMPP-dual-CE MS) method for the profiling of BAs derived from host–gut microbiota cometabolism in mice. Using the proposed method, we discovered two new types of amino acid conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Our lab has recently discovered many new bile acids, for which the MS/MS spectra have been made available as an open access resource. Additionally, we have collected MS/MS data on a historical library of previously determined bile acids. Although other studies have reported the recent discovery of new bile acids as well, unfortunately these could not be included in the current analysis as the corresponding MS/MS data are not publicly available yet. Because our continued study of bile acids has given us a deep understanding of this subset of molecules, we can further analyze these data to understand how specific modifications influence spectrum similarity (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has recently discovered many new bile acids, for which the MS/MS spectra have been made available as an open access resource. Additionally, we have collected MS/MS data on a historical library of previously determined bile acids. Although other studies have reported the recent discovery of new bile acids as well, unfortunately these could not be included in the current analysis as the corresponding MS/MS data are not publicly available yet. Because our continued study of bile acids has given us a deep understanding of this subset of molecules, we can further analyze these data to understand how specific modifications influence spectrum similarity (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, in total, 70 and 35 rare BA–AAs could be detected in IBD mice and healthy mice, respectively (Figure S29 and Table S3). Among them, 55 were identified from the biosamples for the first time. , For healthy mice, rare BA–AAs almost exclusively existed in small intestine (Figure S30). Interestingly, they showed a significant increase in both the intestine and liver of the IBD mice (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…However, identification of these BA–AAs in vivo is challenging due to the lack of reference standards and the poor chromatographic resolution for isomeric backbones. Until now, except for nine rare BA–AAs (CA–Phe, CA–Tyr, CA–Leu, CA–Ala, CA–Pro, DCA–Ala, DCA–Pro, DCA–Leu, and DCA–Phe) from two studies, , the other rare BA–AAs could only be tentatively identified or be detected as in vitro biotransformation products in bacterial cultures …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] Additionally, we have collected MS/MS data on a historical library of previously determined bile acids. Although other studies have reported the recent discovery of new bile acids as well, [31][32][33][34][35][36] unfortunately these could not be included in the current analysis as the corresponding MS/MS data are not publicly available yet. Because our continued study of bile acids has given us a deep understanding of this subset of molecules, we can further analyze these data to understand how specific modifications influence spectrum similarity (Figure 5).…”
Section: Resultsmentioning
confidence: 99%